Province of the Massachusetts-Bay. By the Honourable, the lieutenant governour, &c. Council & Assembly : convened at Boston, upon Wednesday the 27th. of May 1696. In the eighth year of His Majesties reign. For better encouragement to prosecute the French and Indian enemy, &c. (Early English books; 1641-1700 ;, 1696)
Providing for the provision and wages of commanders and companies in the service of the King, and reiterating the offer of bounties for Indian scalps and prisoners. Signed: Isaac Addington, secr. William Stoughton.